2020
DOI: 10.1136/bmjopen-2020-042142
|View full text |Cite
|
Sign up to set email alerts
|

What is spiritual care? Professional perspectives on the concept of spiritual care identified through group concept mapping

Abstract: ObjectivesThe overall study aim was to synthesise understandings and experiences regarding the concept of spiritual care (SC). More specifically, to identify, organise and prioritise experiences with the way SC is conceived and practised by professionals in research and the clinic.DesignGroup concept mapping (GCM).SettingThe study was conducted within a university setting in Denmark.ParticipantsResearchers, students and clinicians working with SC on a daily basis in the clinic and/or through research participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 61 publications
0
55
0
4
Order By: Relevance
“…In line with this finding, Hvidit et al studied the identification, organization, and prioritization of SC experiences and perceptions in researchers, students, and clinical therapists. They found that an unclear definition of SC was a reason for the low implementation of this care (22). Likewise, Holmes found that ambiguity in the definitions of spirituality and religion and the multiplicity of SC provision models confused SC providers in the hospital from the perspectives of managers, policymakers, researchers, and professors (23).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, Hvidit et al studied the identification, organization, and prioritization of SC experiences and perceptions in researchers, students, and clinical therapists. They found that an unclear definition of SC was a reason for the low implementation of this care (22). Likewise, Holmes found that ambiguity in the definitions of spirituality and religion and the multiplicity of SC provision models confused SC providers in the hospital from the perspectives of managers, policymakers, researchers, and professors (23).…”
Section: Discussionmentioning
confidence: 99%
“…To approach spiritual needs through daily interaction with the patient, underlines the need for spiritual care to be included in the curriculum, and the necessity of this has increasingly come into focus during the past decades. In an international context this also needs to be furthered by the concept "spirituality" to be continuously addressed and discussed in research, as the concept has so many different connotations and meanings, as an aspect of being human and as a concept in healthcare (Hvidt et al, 2020). "The Spiritual Assessment in Aging" from the United Kingdom (Nelson-Becker et al, 2007) was developed to both prepare and guide clinicians to undertake spiritual assessment through conversation, identifying 11 domains in spirituality through which a framework is assembled for spiritual assessment with older adults.…”
Section: Phase 1: Identifying Spiritual Needs and Resourcesmentioning
confidence: 99%
“…In our conceptualization of spiritual care, we focus on secular, spiritual and religious existential orientations, needs, and resources in connection with illness and crisis. This understanding is aimed at capturing the potential width of the individual patient in relation to the ontological grounding (la Cour and Hvidt, 2010;Nolan, 2011;Hvidt et al, 2020Hvidt et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Spiritual care might be defined as a “type of care that addresses and seeks to meet existential and spiritual needs and challenges in connection with illness and crisis” (Hvidt et al, 2020 , p. 2), and therefore, it is a shared responsibility of health care professionals to consider patients’ spiritual needs, resources and challenges (Frick, 2017 ). Spiritual care is increasingly recognized as being capable of making a positive contribution to both mental and physical health (Koenig, 2002 ).…”
Section: Introductionmentioning
confidence: 99%